An Overview of The Incidence of Acne Due to The Use of Masks During The COVID-19 Pandemic - Febriyanti, Monica Syefi; Sitanggang, Christanti Naomi Pramasanti; Zebua, Ribka Liliana; Widiyani, Syahfori (SCRIPTA SCORE Scientific Medical Journal, 2024)
Background: On March 11 2020, WHO declared COVID-19 as a pandemic. One of the efforts to prevent, control and break the chain of transmission of COVID-19 in the community is to use a mask. However, apart from feeling uncomfortable, many complaints about acne due to the use of masks are found in the community. During the COVID-19 pandemic, a popular phenomenon appeared on social media, namely "Maskne", a combination of the words mask and acne. Objective: The purpose of this study was to determine the incidence of acne due to the use of masks. Methods: The approach used in this research is quantitative, cross- sectional with data collection techniques through questionnaires. Data analysis using SPSS version 16.0 software. Results: The results showed that the longer use of masks, the higher incidence of acne; the more steps of cleaning the face, the smaller severity of acne. Conclusion: The incidence of acne due to wearing mask during the COVID-19 pandemic correlates with the length of time wearing a mask. The type of mask, the colour of the mask and the variety of beauty products used are not correlated with an increase in the incidence of acne during the use of masks. Keyword: acne, COVID-19, mask, maskne Latar Belakang: Pada tanggal 11 Maret 2020 WHO menyatakan COVID-19 sebagai pandemi. Salah satu upaya pencegahan dan pengendalian, serta pemutusan rantai penularan COVID-19 pada masyarakat adalah dengan menggunakan masker. Namun, selain rasa tidak nyaman, keluhan timbulnya jerawat akibat menggunakan masker banyak ditemukan di masyarakat. Selama pandemi COVID-19 muncul fenomena yang populer pada media sosial yaitu â€œMaskneâ€ gabungan kata mask dan acne. Tujuan: Tujuan penelitian ini adalah mengetahui gambaran kejadian jerawat akibat menggunakan masker selama pandemi dan faktor yang menimbulkan jerawat akibat pemakaian masker. Metode: Pendekatan yang digunakan dalam penelitian ini yaitu kuantitatif, potong lintang dengan teknik pengumpulan data melalui kuesioner. Analisis data dengan menggunakan software SPSS versi 16.0. Hasil: Hasil penelitian didapatkan bahwa semakin lama pemakaian masker maka semakin tinggi angka kejadian jerawat; semakin banyak tahapan membersihkan wajah maka tingkat keparahan jerawat makin kecil. Kesimpulan: Insidensi jerawat akibat penggunaan masker pada pandemi COVID-19 berhubungan dengan lama penggunaan masker. Tipe masker, warna masker, dan jenis produk kecantikan digunakan tidak berhubungan dengan peningkatan insidensi jerawat pada penggunaan masker. Kata Kunci: COVID-19, jerawat, masker, maskne